2020
DOI: 10.21203/rs.3.rs-35287/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the leaf microbiome from whole-genome sequencing data of the 3000 rice genomes project.

Abstract: Background: The crop microbial communities are shaped by interactions between the host, microbes and the environment, however, their relative contribution is beginning to be understood. Here, we explore these interactions in the leaf bacterial community across 3,024 rice accessions. Findings: By using unmapped DNA sequencing reads as microbial reads, we characterized the structure of the rice bacterial microbiome. We identified central bacteria taxa that emerge as microbial “hubs” and may have an influence on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…1B). This is in line with the polygenic architecture reported in GWAS conducted on microbial communities (Horton et al 2014; Walters et al 2018; Bergelson et al 2019; Roman-Reyna et al 2020; Deng et al 2021; Brachi et al 2022; VanWallendael et al 2022). Differences in the number of QTLs among the six ‘plant compartment × seasons’ were barely significant (Generalized Linear Model, GLM, F = 2.30, P = 0.0471).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1B). This is in line with the polygenic architecture reported in GWAS conducted on microbial communities (Horton et al 2014; Walters et al 2018; Bergelson et al 2019; Roman-Reyna et al 2020; Deng et al 2021; Brachi et al 2022; VanWallendael et al 2022). Differences in the number of QTLs among the six ‘plant compartment × seasons’ were barely significant (Generalized Linear Model, GLM, F = 2.30, P = 0.0471).…”
Section: Resultssupporting
confidence: 88%
“…All GWAS performed previously on plant microbial communities were conducted on one specific plant compartment (Walters et al 2018; Roman-Reyna et al 2020; Deng et al 2021; Brachi et al 2022; VanWallendael et al 2022), with the exception of one GWAS conducted on worldwide accessions of A. thaliana at the leaf (Horton et al 2014) and root (Bergelson et al 2019) levels. Similar to our results, this latter GWAS showed a small overlap between the leaf and root compartments in candidate genes associated with descriptors of bacterial and fungal communities (Bergelson et al 2019), which is in line with the adaptive differences in microbial community diversity and composition observed among plant niches, from rhizosphere soils to plant canopies (Müller et al 2016; Cregger et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We used high-yielding commercial cultivars adapted to Northern European conditions, and thus genotypes were highly similar. Detailed studies of host genetic control of microbiome assembly has only recently been initiated [36,37]. For instance, in a recent study in wheat using cultivars having different pathogen resistance genes, it was found that genotype was important for determining the leaf-associated microbiome [38].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the five GWAS [83][84][85][86] and the single genome-environment association study (GEAS) (Roux et al 2022) conducted on the leaf compartment and using bacterial community descriptors as phenotypic traits, revealed a polygenic architecture controlling microbiota assembly, which is in line with the small percentage of variance explained by the phenotyping of individual mutant lines [87]. In agreement with those association genetic studies and the two GWAS conducted on A. thaliana in response to a PGPB strain [47,49], we identified a complex genetic architecture for the response of A. thaliana to 13 non-pathogenic bacterial strains.…”
Section: A Complex and Highly Flexible Genetic Architecture Underlies...mentioning
confidence: 99%